Diagnosis and procedure of traumatic fibroma in a pediatric patient: Case report (Research, Society and Development, 2023)
Traumatic fibroma is a common lesion in the oral cavity, characterized by its benign nature and its frequent association with repeated trauma. Generally, this condition presents as a round or ovoid-shaped protuberance, which may be sessile or pedunculated and exhibit a smooth, pinkish surface. This study aims to report the clinical case of a three-year-old pediatric patient who developed a traumatic fibroid approximately two and a half years ago. The therapeutic approach to this lesion occurred through a surgical procedure, therefore it is important to highlight that traumatic fibroma can be confused with other oral pathologies, thus emphasizing the need for an accurate diagnosis and an appropriate therapeutic approach. Therefore, it is essential to educate parents or guardians about the importance of care in cases of trauma or the emergence of tumors in the oral cavity.